Malaria in Pregnancy: Systematic Review of Maternal and Fetal Outcomes and Effectiveness of Preventive Strategies - Ahmar, Hamdiah; Jayanti, Nur; Jayanti, Ira; Fatmasari, Baiq Dika; Sharief, Suchi Avnalurini (Journal of Current Health Sciences, 2025)
This literature review aims to systematically assess the maternal and fetal health risks associated with malaria infection during pregnancy and evaluate the effectiveness of current prevention and management strategies. A narrative synthesis approach was employed, screening articles published from January 2014 to March 2025 in PubMed, ScienceDirect, and SpringerLink. Of 68 initially identified articles, 20 met the inclusion criteria, focusing on clinical outcomes such as anemia, preeclampsia, low birth weight, and neonatal mortality in malaria-endemic settings. The review demonstrates that malaria during pregnancy significantly increases the risk of maternal anemia (OR 2.40), placental malaria (up to 65.9% in primigravidas), preterm birth (OR 1.65), and neonatal death (OR 1.40), with highest burdens in sub-Saharan Africa and vulnerable groups. Key interventions—intermittent preventive treatment in pregnancy (IPTp) and long-lasting insecticidal nets (LLINs)—consistently reduce these risks, but face implementation barriers such as drug resistance and limited healthcare access. This review highlights the urgent need for further research on malaria vaccination in pregnancy and innovative diagnostic technologies, as well as cross-sectoral efforts to address socioeconomic barriers and strengthen surveillance, policy, and health system capacity. Abstrak: Literature review ini bertujuan untuk menilai secara sistematis risiko kesehatan maternal dan fetal yang terkait dengan infeksi malaria selama kehamilan serta mengevaluasi efektivitas strategi pencegahan dan penatalaksanaan terkini. Pendekatan sintesis naratif digunakan dengan menelaah artikel yang dipublikasikan antara Januari 2014 hingga Maret 2025 di PubMed, ScienceDirect, dan SpringerLink. Dari 68 artikel yang diidentifikasi, 20 memenuhi kriteria inklusi dengan fokus pada luaran klinis seperti anemia, preeklamsia, berat badan lahir rendah, dan kematian neonatal pada wilayah endemis malaria. Hasil tinjauan menunjukkan bahwa malaria selama kehamilan secara signifikan meningkatkan risiko anemia maternal (OR 2,40), malaria plasenta (hingga 65,9% pada primigravida), kelahiran prematur (OR 1,65), dan kematian neonatal (OR 1,40), dengan beban tertinggi di Afrika Sub-Sahara dan kelompok rentan. Intervensi utama—intermittent preventive treatment in pregnancy (IPTp) dan penggunaan kelambu berinsektisida jangka panjang (LLINs)—secara konsisten menurunkan risiko ini, namun masih menghadapi hambatan implementasi seperti resistensi obat dan keterbatasan akses layanan kesehatan. Tinjauan ini menyoroti kebutuhan mendesak akan penelitian lebih lanjut terkait vaksinasi malaria pada kehamilan dan inovasi teknologi diagnostik, serta upaya lintas sektor untuk mengatasi hambatan sosial ekonomi dan memperkuat sistem surveilans, kebijakan, serta kapasitas sistem kesehatan.